We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

In details please ..

and please understand that I struggle a little in English ..

xvxvxv Aug 30, 2014

#5**+13 **

The object falls 5 meters changing E(potential) to E(kinetic), then it goes back up changing E(kinetic) to E(potential). Still it hasn't reached its previous height so there will still be E(kinetic) left. The difference in height from beginning to end is 3 meters: 5 meters (beginning)- 2 meters (end)=3 meters.

Honga Aug 31, 2014

#1**+8 **

17. The red ball will bounce back after collision and move in the same direction the yellow ball went previously. This means the speed must be negative and only one of the answers is negative so answer d seems logical.

=>(Red) (Yellow)<=

(Red)(Yellow)

(Red)<= =>(Yellow)

The red ball will move in the opposite direction so negative speed. So answer D should be correct.

24.

E(potential)=m*g*h=m*9.81*(5-2)=m*29.43

E(kinetic)=1/2*m*v^2

E(kinetic)=E(potential)

1/2*m*v^2=m*29.43

v^2=29.43*2=58.86

v=58.86^(1/2)=7.67

The correct answer is C

Honga Aug 30, 2014

#3**+13 **

In a closed system there is no loss of energy. The potential energy is the energy every object has that can be released by letting it fall, the potential energy will be transformed to kinetic energy (speed).

This means all the energy released by dropping 3 meters (5-2) will go towards kinetic energy. The formula for potential energy is E(potential)=mass*gravitational unit*height, the formula for kinetic energy is E(kinetic)=1/2*mass*velocity^2.

Since E(potential) becomes E(kenetic) you can equate these two kinds of energy, so E(potential)=E(kinetic) (more precisely E(potential_begin)-E(potential_end)=E(kenetic)). The mass is unknown but appears in both formulas so you remove it from both sides, the result is: height (difference in height)*gravitational unit=1/2*velocity^2 which grants you the answer to your question.

Honga Aug 30, 2014

#5**+13 **

Best Answer

The object falls 5 meters changing E(potential) to E(kinetic), then it goes back up changing E(kinetic) to E(potential). Still it hasn't reached its previous height so there will still be E(kinetic) left. The difference in height from beginning to end is 3 meters: 5 meters (beginning)- 2 meters (end)=3 meters.

Honga Aug 31, 2014